2013
DOI: 10.4018/jegr.2013010101
|View full text |Cite
|
Sign up to set email alerts
|

A Success Model for the Malaysian Government e-Procurement System

Abstract: In Malaysia, there has been a tremendous effort in implementing e-government as a national agenda to increase public transparency, improve sector efficiency and effectiveness, and reduce public expenditure through lower operational costs. One of the e-government applications is the ePerolehan, a government-to-business (G2B) system that enables online public procurement coordination and transaction between government and businesses. However, there has been a lack of empirical research findings in evaluating the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 49 publications
1
22
0
Order By: Relevance
“…Vaidyanathan and Devaraj [38] found that the quality of the information flow process, the logistics fulfillment process, and e-procurement satisfaction have a strong relationship. Kassim and Hussin [39] investigated the factors affecting the success of e-procurement for the Malaysian government. Their study shows that transparency, efficiency, and information quality are the most important factors contributing to the success of e-procurement.…”
Section: Information Qualitymentioning
confidence: 99%
“…Vaidyanathan and Devaraj [38] found that the quality of the information flow process, the logistics fulfillment process, and e-procurement satisfaction have a strong relationship. Kassim and Hussin [39] investigated the factors affecting the success of e-procurement for the Malaysian government. Their study shows that transparency, efficiency, and information quality are the most important factors contributing to the success of e-procurement.…”
Section: Information Qualitymentioning
confidence: 99%
“…Most prior studies had been employing only some of the constructs from each element of TOE model towards new technologies adoption [11], [24][25][26][27]. For example, the study by [11] adopted the TOE model to examine the level of e-Perolehan system achievement and the influences that subsidize to this achievement, as professed by the Government employers but the study included only attitude of users, learning of organization, expectation of suppliers, compatibility of the system and imitative pressure. The study by [25] also adopted the TOE model to explore the influence of these factors on the innovation decision of firms in the context of a developing country.…”
Section: I31 Theoretical Gapmentioning
confidence: 99%
“…Studies by [8,9] and [10] would have been more interesting if the authors had explained the indirect influences of performance expectancy towards e-procurement adoption. The study by [11] aimed at investigating the level of e-Perolehan system success and the factors that contribute to this success, as perceived by the Government users. The structural equation modeling was used to analyze the data.…”
Section: Introduction I1 Overview and Problem Settingmentioning
confidence: 99%
“…Thus, it can be concluded that the highest success in achievements is on the improvement of service performance, followed by efficiency, transparency and information quality. The results also show that user attitude has a direct influence on the system usage [4].…”
Section: Literature Reviewmentioning
confidence: 76%
“…They concluded that the document flow process was reduced approximately from 73 to 30 days. Other benefits involved the reduction in printing and copying costs, halved the total costs on telephone and faxing volumes between the owner and contractors [3], while Kassim and Hussin (2013) concluded that use of electronic system explains nearly 69% of the variance in transparency, 87% in service performance, 79% in efficiency and 67% in information quality. Thus, it can be concluded that the highest success in achievements is on the improvement of service performance, followed by efficiency, transparency and information quality.…”
Section: Literature Reviewmentioning
confidence: 99%